Effect of Social Robot's Role and Behavior on Parent-Toddler Interaction - Gvirsman, Omer; Gordon, Goren (2024 19th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2024)
Social robots, designed to interact with people through natural communication modes like speech, body motion, gestures, and facial expressions, have been extensively studied in child-robot interaction for educational purposes. Recently, social robots have been explored in triadic parent-child-robot interactions, showing promise due to their interactivity, computational power, and physical presence, which enable multimodal natural communication and cater to toddlers' developmental stages and physical curiosity. However, these have focused only on shared reading experiences and engaged older children, rather than toddlers. We developed two games, one with two levels of robot scaffolding, and another with either structured or unstructured design. We then explored, in two studies, how a social robot's assigned role and behaviors influence the engagement of parents and toddlers with the robot and their interaction with each other. Our results show that parents affectively scaffolded their children less when the robot increased its scaffolding behaviors and that parents provided more scaffolding in a structured game with the robot, whereas in an unstructured game the dyad exhibited more cooperation in which children exhibited more independence. These findings can contribute to a better understanding of interaction design, triadic dynamics, and the role of the robot in parent-toddler-robot scenario.CCS CONCEPTS*Computer systems organization → Robotics;*Applied computing → Interactive learning environments;*Human-centered computing → Empirical studies in interaction design.